PENGARUH PENGGUNAAN SHOPEE PAYLATER TERHADAP PRILAKU KONSUMTIF DITINJAU DARI PERSPEKTIF EKONOMI SYARIAH - Ilham, Muhammad; Saifullah; Salwa Amor, Gina (Sekolah Tinggi Ekonomi Islam Al-Furqon Prabumulih, 2023)
This study aims to determine the effect of using Shopee Paylater on the consumptive behavior of STAIN Bengkalis Sharia Economics Study Program students. This type of research is quantitative research. The population in this study were 728 students of the Sharia Economics Study Program at STAIN Bengkalis and the sample used was 43 students who used Shopee Paylater. The data collection technique used a questionnaire / questionnaire and the data was processed using SPSS 25. In this study using simple linear regression analysis. The results of this study indicate that partially the variable use of the Shopee Paylater feature has a positive and significant effect on the consumptive behavior of students of the Sharia Economics Study Program at STAIN Bengkalis. This is evidenced by the tcount value of 4,821 with a ttable value of 2,019 besides the significance value of 0.000 which is below 0.05 (significant level). This shows that the tcount value is greater than the ttable (4.821> 2.019). so that there is an influence between the use of Shopee Paylater on the consumptive behavior of students significantly. According to the view of Islamic economics, the Shopee Paylater feature can be utilized. However, its use must be done wisely so as to avoid the badness that Allah SWT prohibits. Limits and teachings in Islamic economics teach us not to behave consumptively.